2014
DOI: 10.1534/genetics.114.167346
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway Controls Border Cell Migration Through Distinct Mechanisms in Outer Border Cells and Polar Cells of the Drosophila Ovary

Abstract: The Hippo pathway is a key signaling cascade in controlling organ size. The core components of this pathway are two kinases, Hippo (Hpo) and Warts (Wts), and a transcriptional coactivator, Yorkie (Yki). Yes-associated protein (YAP, a Yki homolog in mammals) promotes epithelial-mesenchymal transition and cell migration in vitro. Here, we use border cells in the Drosophila ovary as a model to study Hippo pathway functions in cell migration in vivo. During oogenesis, polar cells secrete Unpaired (Upd), which acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 92 publications
8
29
0
1
Order By: Relevance
“…Interestingly, despite that Yki overexpression phenocopies wts knockdown-induced migratory defect (31), we found inhibition of Yki activity under upd promoter is not sufficient to accelerate border cell migration (Fig. S5 A and B), which is consistent with a previous study (31).…”
Section: Jnk Is Required For Hippo Activation-induced Border Cell Migsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, despite that Yki overexpression phenocopies wts knockdown-induced migratory defect (31), we found inhibition of Yki activity under upd promoter is not sufficient to accelerate border cell migration (Fig. S5 A and B), which is consistent with a previous study (31).…”
Section: Jnk Is Required For Hippo Activation-induced Border Cell Migsupporting
confidence: 92%
“…Consistent with our data, both TIA1 and YAP have nucleo-cytoplasmic shuttling ability (7,50,51). Interestingly, recent studies found that hpo and wts are both required for border cell migration during oogenesis (31,32), highlighting the importance of cell migration promoting roles of the Hippo pathway. On the basis of that finding, our data further demonstrate that JNK acts downstream of Hippo pathway in inducing normal border cell migration (Fig.…”
Section: Jnk Is Required For Hippo Activation-induced Border Cell Migsupporting
confidence: 92%
See 2 more Smart Citations
“…In mammalian cell culture, YAP/TAZ activity is also regulated by tension of the actin cytoskeleton (Dupont et al, 2011). These effects may be bidirectional in some cases; the Hippo pathway also regulates the actin cytoskeleton in Drosophila imaginal discs (Fernández et al, 2011; Lin et al, 2014). Other studies suggest that overexpression of Yorkie can directly influence actin levels at wing hair initiation sites (Fang and Adler, 2010).…”
Section: Discussionmentioning
confidence: 99%